2014
DOI: 10.1039/c4gc00854e
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic depolymerization of alkali lignin in subcritical water: influence of formic acid and Pd/C catalyst on the yields of liquid monomeric aromatic products

Abstract: Alkali lignin was subjected to depolymerization in subcritical water at 265 °C, 6.5 MPa for reaction times between 1–6 h in a batch reactor and in the presence of formic acid (FA) and Pd/C catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
112
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 142 publications
(116 citation statements)
references
References 28 publications
4
112
0
Order By: Relevance
“…In addition, Forchheim et al [21] found that the yields of catechol increased with increasing reaction temperature due to favourable reaction kinetics during non-catalytic lignin depolymerization in subcritical water. Onwudili and Williams [19] also reported significant formation of catechol and phenol from guaiacol.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…In addition, Forchheim et al [21] found that the yields of catechol increased with increasing reaction temperature due to favourable reaction kinetics during non-catalytic lignin depolymerization in subcritical water. Onwudili and Williams [19] also reported significant formation of catechol and phenol from guaiacol.…”
Section: Introductionmentioning
confidence: 98%
“…The presence of some organic co-solvents and capping agents has been found to minimize heat-induced polymerization of lignin and its primary degradation products to form char. For instance, the addition of formic acid (FA) has been shown to influence the degradation pathway of lignin via hydrolysis of ether linkages, possible hydrogenolysis of C-C and C-O bonds, and hydrogenation of C=C bonds to produce a variety of compounds [19]. In recent work [19] carried out at 265 °C and 6.5MPa, lignin degraded to produce guaiacol as the dominant product in the absence of formic acid.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gas products were analysed offline by a system of three gas chromatographs (GCs), with already published analytical conditions [20][21]. One of the GC was fitted with a 2 m x 2 mm Molecular Sieve column for the separation of hydrogen, oxygen, nitrogen and CO, which were detected by a thermal conductivity detector (TCD).…”
Section: Gas Analysismentioning
confidence: 99%